Touch of Medical Ethics at the Beginning of Medical School - Nova Ghimire; Dhirendra Yadav (Journal of Nepal Medical Association, 2024)
There comes a great responsibility to make patients feel better with the title of doctor. Often we meet certain moral and ethical dilemmas that cannot be solved by our medical textbook alone. It requires a certain assistance which can only be provided by medical ethics. Medical ethics is the guiding moral that guides Health Care Workers to provide a holistic approach while treating a patient. Medical ethics is the soul that can not only prevent future dilemmas but can overall make a healthcare worker ‘feel’ and have empathy for the patient. From the story of Paul and the true life stories of patients we encountered during our visit to the Leprosy center, we got a sense of empathy. Ethical practice and empathy are the pillars that can play a vital role in the rapidly increasing level of violence against the Health care professionals. So it is an emerging need to have medical ethics as a part of the curriculum among medical students.